Pharmacokinetic study of two acetylcholinesterase reactivators, trimedoxime and newly synthesized oxime K027, in rat plasma - Karasova, Jana Zdarova; Chladek, Jaroslav; Hroch, Milos; Josef, Fusek; Hnidkova, Daniela; Kuca, Kamil (Journal of applied toxicology, 2013)
K027 [1-(4-hydroxyiminomethylpyridinium)-3-(4-carbamoylpyridinium)-propane dibromide] is a promising new reactivator of organophosphate- or organophosphonate-inhibited acetylcholinesterase (AChE) with low acute toxicity and broad spectrum efficacy. The aim of the present study was to compare the pharmacokinetics of both compounds. Male Wistar rats (body weight = 320 ± 10 g) were administered a single intramuscular dose of K027 (22.07 mg kg(-1)) and an equimolar dose of trimedoxime. Blood was collected at various time intervals until 180 min. Plasma samples were analyzed by reversed-phase HPLC with ultraviolet (UV) detection. The recovery of both oximes from the plasma was approximately 90% and a linear relationship (R(2) > 0.998) was observed between the peak areas and concentrations of calibrated standards in the range 1-100 µg ml(-1). Near-identical plasma profiles were obtained for both compounds. No differences were found in the mean ± SD values of C(max) (18.6 ± 2.5 vs 20.0 ± 6.3 µg ml(-1), P = 0.72) and AUC(0-180min) (2290 ± 304 vs 2269 ± 197 min µg ml(-1), P = 0.84). However, the percentage coefficient of variation of the first-order rate constant of absorption (k(a)) was 3-fold higher (P < 0.01) providing evidence for more erratic absorption of intramuscular trimedoxime as compared with K027. In conclusion, oxime K027 might have superior pK properties that may be translated in its faster absorption and subsequent tissue distribution.
Keywords: tkáňová distribuce; Male; Rats, Wistar; Trimedoxime; Tissue Distribution; injekce intramuskulární; vysokoúčinná kapalinová chromatografie; Oximes; mužské pohlaví; trimedoxim; potkani Wistar; Cholinesterase Reactivators; Chromatography, High Pressure Liquid; Pyridinium Compounds; krysa rodu Rattus; Spectrophotometry, Ultraviolet; Animals; pyridinové sloučeniny; zvířata; Rats; reaktivátory cholinesterasy; oximy; Injections, Intramuscular; spektrofotometrie ultrafialová